Retrospective evaluation of cases with pneumothorax in our neonatal intensive care unit - Abdulvahit Aşık; Selahattin Akar (Northwestern Medical Journal)
Aim: This study aimed to retrospectively evaluate the patients who were followed up in the neonatal intensive care unit of our hospital with the diagnosis of pneumothorax.